G420(P) Cost Implication of Non-Adherence with the NICE Guideline Regarding Testing of Stool in Acute Gastroenteritis. (7th April 2014) - Smith, AJ; Reddy, S; Salujia, T; Jayatunga, R
Abstract : Background: Gastroenteritis is very common in children, accounting for a significant proportion of all paediatric admissions in the UK each year. Stool microscopy, culture and sensitivity (MC&S) is usually requested by nurses for any child having loose stools. With NHS spending currently restricted by financial constraints it is imperative to identify unnecessary expenditure and improve cost effectiveness of routine investigations. Clear guidelines were published by the National Institute of Health and Care Excellence (NICE) in 2009 discouraging routine stool sampling, indicating it only where likely to influence further management. Our primary aim was to determine compliance with NICE guidelines in negative stool MC&S performed during an 18 month period. Our secondary aim was to quantify the cost implication of stiool MC&S in the absence of true indication. Methods: A retrospective study of all paediatric stool MC&S samples processed between January 2012 and May 2013 was undertaken. Where stool MC&S was negative, discharge summaries and/or patient notes were reviewed in order to identify the indication for that sample to be sent. Indications were compared against the audit standard, the NICE guidelines. Cost implication of processing stool MC&S without appropriate indication was then calculated. Results: 555 stool MC&S were processed in the 18 month study period; 170 (30.6%) samples were positive and 385 (69.4%) were negative. Of the latter, only 208 (54.0%) were indicated according to NICE guidelines. 177 (46.0%) negative samples were processed in the absence of appropriate indication, accruing an approximate cost implication of over £3000 in the 18 month study period. Conclusion: The majority (69.4%) of stool MC&S performed during the 18 month study period were negative and hence did not influence further management. Of these, only 54.0% were indicated by NICE guidelines. We emphasise the need for compliance with NICE guidelines regarding testing of stool in acute gastroenteritis, which would provide a potential saving of greater than £2000 per annum. ReferencesNational Institute for Health and Care Excellence (2009) Diarrhoea and vomiting in children younger than 5 years. CG84. London: National Institute for Health and Care Excellence.